Teaching and researching computer-assisted language learning - Beatty, Ken (Longman, 2010)
Computers play a crucial and rapidly evolving role in education, particularly in the area of language learning. Far from being a tool mimicking a textbook or teacher, Computer-Assisted Language Learning (CALL) has the power to transform language learning through the pioneering application of innovative research and practices.